Zinc-aluminum-magnesium coated steel plate with excellent degreasing property and manufacturing method thereof

By forming a hydrophilic chemical conversion film with a thickness of ≥20nm on the surface of the zinc-aluminum-magnesium-coated steel plate, the problem of weak degreasability is solved, significantly improving the degreasability and ensuring the continuity of the surface water film.

CN119899994AActive Publication Date: 2025-04-29BAOSHAN IRON & STEEL CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311406007.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The degreasability of zinc-aluminum-magnesium-coated steel plates is weak, resulting in discontinuity of water film on the surface of the steel plate, affecting the subsequent formation of phosphating crystallization and zirconium-forming film, thereby weakening the paint film bonding force and under-film expansion resistance of the electrophoretic layer.

Method used

A hydrophilic chemical conversion film with a thickness of ≥20 nm is formed on the surface of the zinc-aluminum-magnesium-coated steel plate. The film fills the nano-scale grooves on the surface of the coating and passivates the Al particles in the ternary eutectic structure to reduce its van der Waals adsorption force.

Benefits of technology

The degreasability of zinc-aluminum-magnesium-coated steel plate is significantly improved, so that it reaches the same degreasing level as GI or GA coating under severe alkali degreasing conditions, ensuring continuous and complete surface water film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899994A_ABST
    Figure CN119899994A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc-aluminum-magnesium coated steel plate with excellent degreasing property, which comprises a base plate and a zinc-aluminum-magnesium coating, the surface of the zinc-aluminum-magnesium coating is provided with a hydrophilic chemical conversion film, and the chemical conversion film is filled with nano-scale grooves in the eutectic structure of the zinc-aluminum-magnesium coating. Al particles in a ternary eutectic structure of the zinc-aluminum-magnesium coating are passivated; the chemical conversion coating contains salts of Al, Mg and Zn; the thickness of the chemical conversion film is larger than or equal to 20 nm. Correspondingly, the invention further discloses a manufacturing method of the zinc-aluminum-magnesium coated steel plate. The zinc-aluminum-magnesium coated steel plate has excellent degreasing property under the harsh alkali degreasing condition, so that the zinc-aluminum-magnesium coated steel plate can be suitable for automobile structural parts, inner plates and outer plates which have high requirements on the surface quality and the formability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a steel plate and a manufacturing method thereof, and in particular to a coated steel plate and a manufacturing method thereof. Background Art

[0002] Zinc-aluminum-magnesium coated steel sheet is an upgraded product of hot-dip galvanized steel sheet. By adding a certain amount of Al and Mg to the galvanizing solution, the corrosion resistance is significantly improved, while better formability and good weldability can be obtained. In recent years, zinc-aluminum-magnesium coated steel sheet has been increasingly used in car bodies. It can replace continuous hot-dip galvanizing (GI) car body materials by thinning the zinc layer.

[0003] As one of the four major manufacturing processes of automobiles, painting plays a role in protecting the car body from corrosion and beautifying its appearance. In the painting process, the first process is degreasing, which aims to remove the anti-rust oil on the surface of the steel plate and form a continuous water film on the surface of the steel plate. This process has an important impact on the subsequent phosphating crystallization or zirconization film formation.

[0004] On the one hand, unqualified degreasing will cause discontinuous water film on the surface of the steel plate, which may cause floating dirt to directly adhere to the surface of the steel plate and cause electrophoretic defects. On the other hand, it may cause poor phosphating crystallization and significantly low zirconization film weight, thereby weakening the paint film bonding strength and under-film corrosion resistance of the subsequent electrophoretic layer.

[0005] Based on the current research, the degreasing property of zinc-aluminum-magnesium coated steel sheets is significantly weaker, inferior to the GI and GA coated steel sheets currently commonly used in automobile factories. This indicates that there are oil residues on the surface of the zinc-aluminum-magnesium coating, which may further hinder the subsequent phosphating crystallization or zirconization film formation. After further research, it was found that unqualified degreasing of zinc-aluminum-magnesium coated steel sheets has little effect on phosphating crystallization, but significantly reduces the weight of the zirconization film, which in turn seriously weakens the bonding strength of the electrophoretic layer paint film and the resistance to corrosion under the film. Summary of the invention

[0006] One of the purposes of the present invention is to provide a zinc-aluminum-magnesium coated steel sheet with excellent degreasing properties, which has excellent degreasing properties under severe alkaline degreasing conditions, so that it can be suitable for automotive structural parts and inner and outer panels with high requirements on surface quality and formability.

[0007] In order to achieve the above object, the present invention provides a zinc-aluminum-magnesium coated steel sheet with excellent degreasing performance, which comprises a substrate and a zinc-aluminum-magnesium coating, wherein:

[0008] The surface of the zinc-aluminum-magnesium coating has a hydrophilic chemical conversion film, which fills the nano-scale grooves in the eutectic structure of the zinc-aluminum-magnesium coating and passivates (particularly, fully passivates) the Al particles in the ternary eutectic structure of the zinc-aluminum-magnesium coating;

[0009] The chemical conversion film contains salts of Al, Mg and Zn;

[0010] The thickness of the chemical conversion film is ≥20nm.

[0011] The salts of Al, Mg and Zn contained in the chemical conversion film of the present invention may be inorganic salts or organic salts.

[0012] Through extensive research, the inventors found that under harsh alkaline degreasing conditions (similar to the degreasing conditions of the paint production line in an automobile factory), that is, the degreasing liquid contains anti-rust oil (for example, the alkaline degreasing liquid contains 2-4g / L of anti-rust oil), the anti-rust oil consumes a large amount of surfactant, which significantly reduces the degreasing ability of the degreasing liquid. The degreasing property of zinc-aluminum-magnesium coated steel plates is significantly weaker, inferior to that of GI and GA coated steel plates.

[0013] If the degreasing of zinc-aluminum-magnesium coated steel plates is unqualified, on the one hand, it will cause the water film on the surface of the steel plate to be discontinuous, causing floating dirt to directly adhere to the surface of the steel plate and increase the probability of electrophoretic defects. On the other hand, it will make the weight of the zirconization film significantly lower, which will seriously weaken the bonding strength of the electrophoretic layer paint film and the resistance to under-film corrosion.

[0014] The inventors have found through research that the weak degreasing property of zinc-aluminum-magnesium coated steel sheets is closely related to the multiphase structure of the coating surface. For zinc-aluminum-magnesium coated steel sheets, the zinc-aluminum-magnesium coating surface has: primary zinc phase + binary eutectic structure (Zn / MgZn2) + ternary eutectic structure (Zn / MgZn2 / Al). Among them, the ternary eutectic structure is relatively dense, and tiny nano-scale Al particles are deeply hidden in the nano-scale microscopic grooves of the eutectic. The Al particles and the tiny gaps around them have a strong adsorption effect on oil particles, especially there is a strong van der Waals adsorption force between Al particles and oil particles. When the content of surfactant in the degreasing liquid is low, on the one hand, it is difficult for the surfactant to penetrate into the tiny gaps of the ternary eutectic to capture oil particles. On the other hand, the surfactant that reaches the gap is too small to take away the oil droplets strongly adsorbed by the Al particles, resulting in unqualified degreasing, which is manifested as a discontinuous water film on the plate surface.

[0015] Based on the above research findings, the inventors of this case immersed the steel plate in an acidic or alkaline electrolyte solution and then took it out and dried it. The zinc-aluminum-magnesium coating reacted with the electrolyte to form a chemical conversion film with a thickness of ≥20nm on its surface. The chemical conversion film thus contains inorganic or organic salts of Al, Mg, and Zn, and the chemical conversion film is hydrophilic. The chemical conversion film partially fills the nano-scale grooves in the eutectic structure on the surface of the coating at the microscopic level. More importantly, the Al particles are partially dissolved in the electrolyte or are fully passivated to form inorganic or organic salt particles of Al, which significantly reduces the van der Waals adsorption force. These triple effects significantly reduce the storage and adsorption of oil particles on the surface of the zinc-aluminum-magnesium coating, significantly improve its degreasing ability, and reach the same degreasing level as GI coating or GA coating.

[0016] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the thickness of the chemical conversion film is 20-500nm.

[0017] As mentioned above, when the thickness of the chemical conversion film is too low, it cannot improve the degreasing performance. However, the inventors have found through experiments and research that when the thickness of the chemical conversion film is too large, it will also affect the subsequent phosphating crystallization and zirconization film formation. Based on this, in a preferred embodiment of the present invention, the thickness of the chemical conversion film is controlled to be 20-500nm.

[0018] Furthermore, in the zinc-aluminum-magnesium coated steel plate described in the present invention, the surface roughness Ra value of the zinc-aluminum-magnesium coating is 0.6-1.8 μm.

[0019] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the zinc-aluminum-magnesium coating contains Mg: 0.8-4.0wt%, Al: 1.0-7.0wt%.

[0020] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the zinc-aluminum-magnesium coating contains Mg: 2.0-4.0wt%, Al: 5.0-7.0wt%.

[0021] It can be seen that the present invention is applicable to medium aluminum-zinc-aluminum-magnesium coated steel plates.

[0022] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the zinc-aluminum-magnesium coating contains Mg: 0.8-3.5wt%, Al: 1.0-5.0wt%.

[0023] It can be seen that the present invention is also applicable to low-aluminum-zinc-aluminum-magnesium coated steel sheets.

[0024] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the chemical conversion film also has a hydrophilic organic film layer, and the organic film layer has polar functional groups.

[0025] In this embodiment, an organic film layer can be formed on the surface of the chemical conversion film. The surface of the organic film layer has more polar functional groups, which enables it to adsorb water well after degreasing, thereby further ensuring the continuity and integrity of the water film on the surface of the coated steel plate.

[0026] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the polar functional groups include at least 3 carboxyl functional groups or 2 hydroxyl functional groups.

[0027] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the organic film layer contains acrylic resin or epoxy resin.

[0028] In order to achieve the technical effect of the present invention, the organic film layer must have two properties: one is a high degree of cross-linking to ensure compactness, and the other is a large number of polar functional groups to ensure hydrophilicity. Acrylic resin or epoxy resin can meet the above two requirements at the same time. The acrylic acid, a polymerization monomer of acrylic resin, contains carboxyl groups, which can undergo self-cross-linking reaction to form a dense cross-linked structure. At the same time, the resin contains a large number of carboxyl groups. A considerable number of strongly polar functional groups ensure the hydrophilicity of the film layer. Epoxy resin is condensed from epoxypropane and bisphenol A, has a high degree of cross-linking and has a large number of polar functional groups OH, which ensures good adsorption of water on the surface of the film layer.

[0029] Furthermore, in the zinc-aluminum-magnesium coated steel sheet described in the present invention, the thickness of the organic film layer is 20-200nm.

[0030] The inventors have found through experiments and research that if the thickness of the organic film layer is too small, the effect is poor, and if the thickness is too large, it will affect the subsequent welding, phosphating crystallization and zirconization film formation. Based on this, in a preferred embodiment of the present invention, the thickness of the chemical conversion film is controlled to be 20-200nm.

[0031] Furthermore, the zinc-aluminum-magnesium coated steel plate described in the present invention has a degreasing water hanging rate of >95% after degreasing and washing under severe alkaline degreasing conditions, and the severe alkaline degreasing conditions include the alkaline degreasing solution containing 2-4g / L of anti-rust oil.

[0032] Another object of the present invention is to provide a method for manufacturing a zinc-aluminum-magnesium coated steel sheet with excellent degreasing properties. The zinc-aluminum-magnesium coated steel sheet obtained by this method has excellent degreasing properties under severe alkaline degreasing conditions, so that it can be suitable for automotive structural parts and inner and outer panels with high requirements on surface quality and formability.

[0033] Based on the above invention object, the present invention also provides a method for manufacturing the zinc-aluminum-magnesium coated steel sheet as described above, which comprises the steps of:

[0034] The substrate is hot-dip plated to obtain a zinc-aluminum-magnesium coated steel sheet;

[0035] The zinc-aluminum-magnesium coated steel sheet is immersed in an acidic or alkaline electrolyte solution for surface treatment and then dried to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating.

[0036] Furthermore, in the manufacturing method of the present invention, when an acidic electrolyte solution is used, the pH value thereof is 2-6; when an alkaline electrolyte solution is used, the pH value thereof is 8-13.

[0037] When the pH of the acidic electrolyte solution used is too low, the acidity is too strong and the reaction is too violent, which may cause excessive erosion of the coating, thereby bringing the risk of microscopic holes on the surface of the coating. When the pH is too high, the reactivity is insufficient and it is difficult to produce an effective film layer. The pH value range of the alkaline electrolyte solution is also based on similar considerations.

[0038] Furthermore, in the manufacturing method described in the present invention, the acidic electrolyte solution contains at least one of the following: permanganic acid, hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, selenic acid, hydrobromic acid, hydroiodic acid, chloric acid, carbonic acid, acetic acid, sulfurous acid, hypochlorous acid, hydrosulfuric acid, silicic acid, aluminic acid, formic acid, acetic acid, oxalic acid, tartaric acid, citric acid, and salicylic acid.

[0039] Furthermore, in the manufacturing method described in the present invention, the alkaline electrolyte solution contains at least one of the following: sodium hydroxide, potassium hydroxide, barium hydroxide, sodium pyrophosphate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, potassium citrate, and ammonia water.

[0040] Furthermore, in the manufacturing method of the present invention, after the surface treatment step, the step of oiling is also included.

[0041] Furthermore, in the oiling step, the amount of oil applied on one side can be 300-1800 mg / m 2 .

[0042] The present invention also provides another method for manufacturing the zinc-aluminum-magnesium coated steel sheet as described above, which comprises the steps of:

[0043] The substrate is hot-dip plated to obtain a zinc-aluminum-magnesium coated steel sheet;

[0044] The zinc-aluminum-magnesium coated steel sheet is immersed in an acidic or alkaline electrolyte solution and then dried to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating;

[0045] A water-based treatment agent is coated on the surface of the zinc-aluminum-magnesium coating obtained in the previous step, and heated and cured to form a hydrophilic organic film layer on the surface of the chemical conversion film.

[0046] Furthermore, in the manufacturing method of the present invention, when an acidic electrolyte solution is used, the pH value thereof is 2-6; when an alkaline electrolyte solution is used, the pH value thereof is 8-13.

[0047] Furthermore, in the manufacturing method of the present invention, the water-based treatment agent contains:

[0048] 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin;

[0049] Nano silicon dioxide 5-15wt%;

[0050] Silane coupling agent 5-10wt%.

[0051] Furthermore, in the manufacturing method of the present invention, the mass percentage ratio of each component of the water-based treatment agent is:

[0052] 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin;

[0053] Nano silicon dioxide 5-15wt%;

[0054] Silane coupling agent 5-10wt%;

[0055] The balance is water and other inevitable impurities.

[0056] In this embodiment: water-soluble acrylic resin or water-soluble epoxy resin is the main film-forming agent. When the content is too low, the number of polar functional groups in the film layer is insufficient, and its hydrophilicity is poor. When the content is too high, the uniformity of the solution formed is insufficient and precipitation is easy to occur. Therefore, it is preferably controlled to be 25-50wt%. Nano silicon dioxide is an additive, which is mainly used to enhance the compactness of the film layer, prevent moisture from penetrating into the film layer, and improve the corrosion resistance of the coating. In addition, it can improve the viscosity of the surface treatment solution to a certain extent. When it is too low, the effect is limited, and when it is too high, it is difficult to dissolve completely. It is preferably controlled to be in the range of 5-15wt%. Silane coupling agent is a film-forming auxiliary agent, which can further improve the crosslinking degree of the film layer and enhance the adhesion between the film layer and the coating. When it is too low, the effect is limited, and when it is too high, the stability of the formulation system is poor. It is preferably controlled to be in the range of 5-10wt%.

[0057] Furthermore, in the manufacturing method of the present invention, the temperature of heating and curing is 100-140° C., and the heating and curing time is 5-15 s.

[0058] Furthermore, in the manufacturing method of the present invention, after the heating and curing step, the step of: oiling is also included.

[0059] Furthermore, in the oiling step, the amount of oil applied on one side can be 300-1800 mg / m 2 .

[0060] The zinc-aluminum-magnesium coated steel sheet with excellent degreasing performance and the manufacturing method thereof of the present invention have the following advantages and beneficial effects:

[0061] The zinc-aluminum-magnesium coated steel sheet with excellent degreasing property described in the present invention uses an electrolyte to treat the steel sheet surface, so that the zinc-aluminum-magnesium coating reacts with the electrolyte to form a chemical conversion film with a thickness of ≥20nm on the surface. The chemical conversion film thus contains inorganic salts or organic salts of Al, Mg, and Zn, and the chemical conversion film is hydrophilic. The chemical conversion film microscopically fills the nano-scale grooves in the eutectic structure on the surface of the coating. More importantly, the Al particles are partially dissolved in the electrolyte or are fully passivated to form inorganic salts or organic salt particles of Al, which significantly reduces the van der Waals adsorption force. These triple effects significantly reduce the storage and adsorption of oil particles on the surface of the coating, thereby significantly improving its degreasing property.

[0062] The zinc-aluminum-magnesium coated steel plate of the present invention has a degreasing water hanging rate of >95% after degreasing and washing under severe alkaline degreasing conditions in which the alkaline degreasing solution contains 2-4g / L of anti-rust oil, and the degreasing property is significantly improved, reaching the same level as GI coating or GA coating, so that it can be applied to automotive structural parts and inner and outer panels with high requirements on surface quality and formability.

[0063] In some embodiments, an organic film layer is also formed on the chemical conversion film, which isolates the penetration of the anti-rust oil film, avoids the contact between the coating and the oil, and completely eliminates the possibility of the nano-grooves and Al particles in the eutectic structure adsorbing oil particles, thereby making the surface oil film easy to degrease and remove. In addition, the surface of the organic film layer has more polar functional groups, so that it can be well adsorbed with water after degreasing, thereby ensuring that the water film on the surface of the coated steel plate is continuous and complete. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 This is a schematic diagram of the cross-sectional structure of the zinc-aluminum-magnesium coated steel plate with excellent degreasing properties described in the present invention.

[0065] Figure 2 The surface structure of the zinc-aluminum-magnesium coating of Comparative Example 1 is shown.

[0066] Figure 3 This is a local enlarged view of the ternary eutectic structure on the surface of the zinc-aluminum-magnesium coating of comparative example 1. DETAILED DESCRIPTION

[0067] The zinc-aluminum-magnesium coated steel sheet with excellent degreasing properties and the method for manufacturing the same described in the present invention will be further explained and illustrated below in conjunction with specific embodiments. However, such explanation and illustration do not constitute an improper limitation on the technical solution of the present invention.

[0068] Examples 1-15

[0069] The zinc-aluminum-magnesium coated steel sheets of Examples 1-5 are all prepared by the following steps:

[0070] The substrate is sequentially subjected to hot-dip galvanizing, leveling, surface treatment, oiling and coiling to obtain a zinc-aluminum-magnesium coated steel sheet.

[0071] Figure 1 This is a schematic diagram of the cross-sectional structure of the zinc-aluminum-magnesium coated steel plate with excellent degreasing properties described in the present invention.

[0072] like Figure 1 As shown, the zinc-aluminum-magnesium coated steel sheet of the present invention comprises a substrate 1 and a zinc-aluminum-magnesium coating 2. In addition, the improvement of the present invention is that a chemical conversion film 3 is formed on the surface of the zinc-aluminum-magnesium coating 2.

[0073] In Examples 1-5 of the present invention, the specific steps of the surface treatment are: immersing the steel plate in an acidic electrolyte solution with a pH of 2-6 and a temperature of 35-40°C for 5-40 seconds, then taking it out and drying it, and the drying temperature is ≥60°C, so as to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating. The chemical conversion film fills the nano-scale grooves in the eutectic structure of the zinc-aluminum-magnesium coating, and fully passivates the Al particles in the ternary eutectic structure of the zinc-aluminum-magnesium coating. The chemical conversion film contains salts of Al, Mg, and Zn, and the thickness of the chemical conversion film is ≥20nm.

[0074] The zinc-aluminum-magnesium coated steel sheets of Examples 6-10 are all prepared by the following steps:

[0075] The substrate is sequentially subjected to hot-dip galvanizing, leveling, surface treatment, oiling and coiling to obtain a zinc-aluminum-magnesium coated steel sheet.

[0076] The specific steps of the surface treatment are: immersing the steel plate in an alkaline electrolyte solution with a pH of 8-13 and a temperature of 35-40°C for 5-40 seconds, then taking it out and drying it, and the drying temperature is ≥60°C, so as to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating. The chemical conversion film fills the nano-scale grooves in the eutectic structure of the zinc-aluminum-magnesium coating, and fully passivates the Al particles in the ternary eutectic structure of the zinc-aluminum-magnesium coating. The chemical conversion film contains salts of Al, Mg, and Zn, and the thickness of the chemical conversion film is ≥20nm.

[0077] The zinc-aluminum-magnesium coated steel sheets of Examples 11-13 were all prepared by the following steps:

[0078] The substrate is sequentially subjected to hot-dip galvanizing, leveling, surface treatment, coating with a water-based treatment agent, heating and curing, oiling and coiling to obtain a zinc-aluminum-magnesium coated steel sheet.

[0079] The specific steps of the surface treatment are: immersing the steel plate in an acidic electrolyte solution with a pH of 2-6 and a temperature of 25-50°C for 5-40s, then taking it out and drying it, and the drying temperature is ≥60°C, so as to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating. The chemical conversion film fills the nano-scale grooves in the eutectic structure of the zinc-aluminum-magnesium coating, and fully passivates the Al particles in the ternary eutectic structure of the zinc-aluminum-magnesium coating. The chemical conversion film contains salts of Al, Mg, and Zn, and the thickness of the chemical conversion film is ≥20nm.

[0080] The specific steps of coating the water-based treatment agent are: using a roller coater to coat the water-based treatment agent on the surface of the chemical conversion film, and using hot air or infrared induction heating to cure it to form a hydrophilic organic film layer on the surface of the chemical conversion film, the organic film layer has polar functional groups, and the thickness of the organic film layer is ≥20nm.

[0081] The composition ratio of the water-based treatment agent is: 5-15% of nano silicon dioxide, 5-10% of silane coupling agent, 25-50% of water-soluble acrylic resin or water-soluble epoxy resin, and the rest of the composition is water and unavoidable impurities.

[0082] In some embodiments, during heat curing, the plate temperature may be controlled to be 100 to 140° C., and the heating time may be 5 to 15 seconds.

[0083] The zinc-aluminum-magnesium coated steel sheets of Examples 14-15 are all prepared by the following steps:

[0084] The substrate is sequentially subjected to hot-dip galvanizing, leveling, surface treatment, coating with a water-based treatment agent, heating and curing, oiling and coiling to obtain a zinc-aluminum-magnesium coated steel sheet.

[0085] The specific steps of the surface treatment are: immersing the steel plate in an alkaline electrolyte solution with a pH of 8-13 and a temperature of 25-50°C for 2-15s, then taking it out and drying it, with a drying temperature of ≥60°C, so as to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating. The chemical conversion film fills the nano-scale grooves in the eutectic structure of the zinc-aluminum-magnesium coating and fully passivates the Al particles in the ternary eutectic structure of the zinc-aluminum-magnesium coating. The chemical conversion film contains salts of Al, Mg, and Zn, and the thickness of the chemical conversion film is ≥20nm.

[0086] The specific steps of coating the water-based treatment agent are: using a roller coater to coat the water-based treatment agent on the surface of the chemical conversion film, and using hot air or infrared induction heating to cure it to form a hydrophilic organic film layer on the surface of the chemical conversion film, the organic film layer has polar functional groups, and the thickness of the organic film layer is ≥20nm.

[0087] The composition ratio of the water-based treatment agent is: 5-15% of nano silicon dioxide, 5-10% of silane coupling agent, 25-50% of water-soluble acrylic resin or water-soluble epoxy resin, and the rest of the composition is water and unavoidable impurities.

[0088] In some embodiments, during heat curing, the plate temperature may be controlled to be 100 to 140° C., and the heating time may be 5 to 15 seconds.

[0089] In some embodiments, during the oiling step, the amount of oil applied on one side can be controlled to be 300-1800 mg / m 2 .

[0090] Comparative Examples 1-5

[0091] The zinc-aluminum-magnesium coated steel sheets of Comparative Examples 1-5 were prepared by the following method:

[0092] The substrate was hot-dip coated, leveled, oiled and coiled in sequence to obtain a comparative zinc-aluminum-magnesium coated steel sheet. It can be seen that none of the comparative examples 1-5 was subjected to surface treatment, and therefore the coating surface did not have a chemical conversion film.

[0093] Table 1 lists the coating chemical element contents of the zinc-aluminum-magnesium coated steel sheets of Examples 1-15 and Comparative Examples 1-5.

[0094] Table 1. (wt%, the balance is Zn and other inevitable impurities)

[0095] Mg Al Example 1 0.8 1.0 Example 2 1.1 1.4 Example 3 1.2 1.7 Example 4 1.4 2.2 Example 5 1.6 2.5 Example 6 2.0 3.2 Example 7 2.2 3.5 Example 8 2.4 4.0 Example 9 2.5 4.2 Example 10 2.5 4.7 Embodiment 11 2.8 5.1 Example 12 3.2 5.6 Embodiment 13 3.5 6.2 Embodiment 14 3.8 6.5 Embodiment 15 4.0 7.0 Comparative Example 1 0.8 1.0 Comparative Example 2 1.6 2.5 Comparative Example 3 2.4 4.0 Comparative Example 4 3.2 5.6 Comparative Example 5 4.0 7.0

[0096] Table 2 lists the specific process parameters of the surface treatment steps of Examples 1-15.

[0097] Table 2.

[0098]

[0099]

[0100] Table 3 lists the specific process parameters for coating water-based treatment agent, heating curing and oiling of Examples 1-15.

[0101] Table 3.

[0102]

[0103] Note: In Table 2, Examples 12, 14, and 15 use water-soluble acrylic resins, and Examples 11 and 13 use water-soluble epoxy resins.

[0104] In addition, the “type of polar functional group” in Table 2 was measured by infrared spectrometer, and the “number of polar functional groups” was measured by X-ray photoelectron spectroscopy.

[0105] In order to verify the degreasing performance of the zinc-aluminum-magnesium coated steel sheets described in the present invention, the zinc-aluminum-magnesium coated steel sheets of the above-mentioned Examples 1-15 and Comparative Examples 1-5 were degreased and then washed with water. The specific degreasing and washing processes are listed in Table 4.

[0106] Table 4. Degreasing and washing process parameters

[0107]

[0108] After degreasing and washing the examples 1-15 and the comparative examples 1-5, the water hanging rate (i.e. the percentage of the water hanging area to the whole board surface area) was measured and the results are shown in Table 5.

[0109] Table 5.

[0110] serial number Degreasing and water hanging rate Example 1 100% Example 2 100% Example 3 100% Example 4 100% Example 5 100% Example 6 100% Example 7 100% Example 8 100% Example 9 100% Example 10 100% Embodiment 11 100% Example 12 100% Embodiment 13 100% Embodiment 14 100% Embodiment 15 100% Comparative Example 1 0% Comparative Example 2 5% Comparative Example 3 5% Comparative Example 4 10% Comparative Example 5 10%

[0111] As shown in Table 5, under the degreasing process shown in Table 4, the water hanging rate of the zinc-aluminum-magnesium coated steel plates of Examples 1-15 of the present invention is 100%, reaching the degreasing and water hanging rate of GI and GA coated steel plates currently used in automobile factories.

[0112] The degreasing and water-hanging rates of the zinc-aluminum-magnesium coated steel sheets of comparative examples 1-5 are only 0-10%, which indicates that the degreasing properties of the zinc-aluminum-magnesium coated steel sheets of comparative examples 1-5 without chemical conversion films are significantly weak.

[0113] Figure 2 The surface structure of the zinc-aluminum-magnesium coating of Comparative Example 1 is shown.

[0114] like Figure 2 As shown, the surface structure of the zinc-aluminum-magnesium coating has: primary zinc phase + binary eutectic structure (Zn / MgZn2) + ternary eutectic structure (Zn / MgZn2 / Al).

[0115] Figure 3 This is a local enlarged view of the ternary eutectic structure on the surface of the zinc-aluminum-magnesium coating of comparative example 1 of the present invention.

[0116] like Figure 3 As shown, it can be seen that the ternary eutectic structure is relatively dense, and tiny nano-scale Al particles are deeply hidden in the nano-scale microscopic grooves of the eutectic. There is a strong adsorption effect between the Al particles and the tiny gaps around them on the oil particles, especially the Al particles and the oil particles have a strong van der Waals adsorption force. When the surfactant content in the degreasing liquid is low, on the one hand, it is difficult for the surfactant to penetrate into the tiny gaps of the ternary eutectic to capture the oil particles. On the other hand, the surfactant that reaches the gap is too small to take away the oil droplets strongly adsorbed by the Al particles. Therefore, the degreasing is unqualified, and the macroscopic manifestation is the discontinuity of the water film on the plate surface.

[0117] The zinc-aluminum-magnesium coated steel sheet with excellent degreasing property described in the present invention is surface treated with an electrolyte, so that the zinc-aluminum-magnesium coating reacts with the electrolyte to form a chemical conversion film with a thickness of ≥20nm on the surface. The chemical conversion film partially fills the nano-scale grooves in the eutectic structure on the surface of the coating at the microscopic level. More importantly, the Al particles are partially dissolved in the electrolyte or are fully passivated to form inorganic salt or organic salt particles of Al, which significantly reduces the van der Waals adsorption force. These triple effects significantly reduce the storage and adsorption of oil particles on the surface of the coating, thereby significantly improving the degreasing property.

[0118] In Examples 11-15 of the present invention, an organic film layer is also formed on the chemical conversion film, which further isolates the penetration of the anti-rust oil film, avoids the contact between the coating and the oil, and completely eliminates the possibility of the nano-grooves and Al particles in the eutectic structure adsorbing oil particles, thereby making the surface oil film easy to degrease and remove. In addition, the surface of the organic film layer has more polar functional groups, so that it can be well adsorbed with water after degreasing, thereby further ensuring that the water film on the surface of the coated steel plate is continuous and complete.

[0119] It should be noted that the combination of the various technical features in this case is not limited to the combination described in the claims of this case or the combination described in the specific embodiments. All technical features recorded in this case can be freely combined or combined in any way unless there is a contradiction between them.

[0120] It should also be noted that the above-listed embodiments are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and similar changes or modifications made therewith can be directly derived or easily associated with the contents disclosed by those skilled in the art from the present invention, and all should belong to the protection scope of the present invention.

Claims

1. A zinc-aluminum-magnesium coated steel sheet with excellent degreasing performance, comprising a substrate and a zinc-aluminum-magnesium coating, characterized in that: The surface of the zinc-aluminum-magnesium coating has a hydrophilic chemical conversion film, which fills the nano-scale grooves in the eutectic structure of the zinc-aluminum-magnesium coating and passivates the Al particles in the ternary eutectic structure of the zinc-aluminum-magnesium coating; The chemical conversion film contains salts of Al, Mg and Zn; The thickness of the chemical conversion film is ≥20nm.

2. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The thickness of the chemical conversion film is 20-500 nm.

3. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The surface roughness Ra value of the zinc-aluminum-magnesium coating is 0.6-1.8 μm.

4. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The zinc-aluminum-magnesium coating contains Mg: 0.8-4.0wt% and Al: 1.0-7.0wt%.

5. The zinc-aluminum-magnesium coated steel sheet according to claim 4, characterized in that: The zinc-aluminum-magnesium coating contains Mg: 2.0-4.0wt% and Al: 5.0-7.0wt%.

6. The zinc-aluminum-magnesium coated steel sheet according to claim 4, characterized in that: The zinc-aluminum-magnesium coating contains Mg: 0.8-3.5wt% and Al: 1.0-5.0wt%.

7. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The chemical conversion film also has a hydrophilic organic film layer, and the organic film layer has a polar functional group.

8. The zinc-aluminum-magnesium coated steel sheet according to claim 7, characterized in that: The polar functional groups include at least 3 carboxyl functional groups or 2 hydroxyl functional groups.

9. The zinc-aluminum-magnesium coated steel sheet according to claim 7, characterized in that: The organic film layer contains acrylic resin or epoxy resin.

10. The zinc-aluminum-magnesium coated steel sheet according to claim 7, characterized in that: The thickness of the organic film layer is 20-200 nm.

11. The zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: Under the severe alkali degreasing conditions, the degreasing water hanging rate after degreasing and washing is greater than 95%, and the severe alkali degreasing conditions include the alkali degreasing liquid containing 2-4g / L of anti-rust oil.

12. The method for manufacturing a zinc-aluminum-magnesium coated steel sheet according to any one of claims 1 to 6 and 11, characterized in that: Includes steps: The substrate is hot-dip plated to obtain a zinc-aluminum-magnesium coated steel sheet; The zinc-aluminum-magnesium coated steel sheet is immersed in an acidic or alkaline electrolyte solution for surface treatment and then dried to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating.

13. The manufacturing method according to claim 12, characterized in that: When an acidic electrolyte solution is used, the pH value is 2-6; when an alkaline electrolyte solution is used, the pH value is 8-13.

14. The manufacturing method according to claim 12, characterized in that: The acidic electrolyte solution contains at least one of the following: permanganic acid, hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, selenic acid, hydrobromic acid, hydroiodic acid, chloric acid, carbonic acid, acetic acid, sulfurous acid, hypochlorous acid, hydrosulfuric acid, silicic acid, aluminic acid, formic acid, acetic acid, oxalic acid, tartaric acid, citric acid, and salicylic acid.

15. The manufacturing method according to claim 12, characterized in that: The alkaline electrolyte solution contains at least one of the following: sodium hydroxide, potassium hydroxide, barium hydroxide, sodium pyrophosphate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, potassium citrate, and ammonia water.

16. The manufacturing method according to claim 12, characterized in that: The surface treatment step further includes the step of oiling.

17. The manufacturing method according to claim 16, characterized in that: In the oiling step, the amount of oil applied on one side is 300-1800 mg / m 2 .

18. The method for manufacturing a zinc-aluminum-magnesium coated steel sheet according to any one of claims 7 to 10, characterized in that: Includes steps: The substrate is hot-dip plated to obtain a zinc-aluminum-magnesium coated steel sheet; The zinc-aluminum-magnesium coated steel sheet is immersed in an acidic or alkaline electrolyte solution and then dried to form a hydrophilic chemical conversion film on the surface of the zinc-aluminum-magnesium coating; A water-based treatment agent is coated on the surface of the zinc-aluminum-magnesium coating obtained in the previous step, and heated and cured to form a hydrophilic organic film layer on the surface of the chemical conversion film.

19. The manufacturing method according to claim 18, characterized in that: When an acidic electrolyte solution is used, the pH value is 2-6; when an alkaline electrolyte solution is used, the pH value is 8-13.

20. The manufacturing method according to claim 18, characterized in that: The water-based treatment agent contains: 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin; Nano silicon dioxide 5-15wt%; Silane coupling agent 5-10wt%.

21. The manufacturing method according to claim 20, characterized in that: The mass percentage ratio of each component of the water-based treatment agent is: 25-50wt% of water-soluble acrylic resin or water-soluble epoxy resin; Nano silicon dioxide 5-15wt%; Silane coupling agent 5-10wt%; The balance is water and other inevitable impurities.

22. The manufacturing method according to claim 18, characterized in that: The temperature of heating and curing is 100-140°C, and the heating and curing time is 5-15s.

23. The manufacturing method according to claim 18, characterized in that: After the heating and curing step, the method further comprises the step of applying oil.

24. The manufacturing method according to claim 23, characterized in that: In the oiling step, the amount of oil applied on one side is 300-1800 mg / m 2 .

Citation Information

Patent Citations

  • Zinc-aluminum-magnesium plating layer surface treating agent as well as preparation method and use method thereof

    CN112538306A

  • Zinc-aluminum-magnesium coated steel plate with excellent adhesive performance and manufacturing method thereof

    CN113122790A

  • Zinc-magnesium-aluminum coated steel plate with excellent blackening resistance and adhesive performance and preparation method of zinc-magnesium-aluminum coated steel plate

    CN113832425A

  • Metal plate processing method and metal plate processed by method

    CN114555862A

  • Zinc-magnesium-aluminum coated steel plate with excellent degreasing and pretreatment performance and manufacturing method

    CN115198219A